Gas exhaust in the Wendelstein 7-X stellarator during the first divertor operation. (1st September 2022) - Wenzel, U.; Schlisio, G.; Drewelow, P.; Krychowiak, M.; König, R.; Pedersen, T.S.; Bozhenkov, S.; Haak, V.; Kharwandikar, A.K.; Lazerson, S.; Naujoks, D.; Perseo, V.; et al.
Abstract: The optimized superconducting stellarator Wendelstein 7-X (W7-X) is equipped with an island divertor for energy control and efficient pumping. We investigated the performance of the island divertor in terms of gas exhaust. For this purpose we have installed 18 pressure gauges in the vacuum vessel. This allowed us to determine the exhaust efficiency, the leakage, the collection efficiency and the compression ratio of the island divertor. These quantities depended strongly on the magnetic configuration. The best performance was obtained in the high-iota configuration. The exhaust efficiency was 2.9%, significantly higher than in the standard configuration (0.44%), and the maximum neutral compression was about 80. The high-iota configuration appears particularly promising for long-pulse operation of W7-X.